MU AND KAPPA OPIOIDS MODULATE MOUSE EMBRYONIC STEM CELL DERIVED NEURAL PROGENITOR DIFFERENTIATION VIA MAP KINASES - Hahn, Jason W. (2009)
Since embryonic stem cell-derived neural progenitors (NPs) have the potential to be used in cell replacement therapy, an understanding of the signaling mechanisms that regulate their terminal differentiation is imperative. In previous studies, we discovered the presence of functional μ opioid receptors (MOR) and κ opioid receptors (KOR) in mouse embryonic stem cells and NPs. Here, MOR and KOR immunoreactivity was detected in NP-derived oligodendrocytes during three stages of their maturation in vitro. Moreover, we examined the modulation of retinoic acid-induced NP differentiation to astrocytes and neurons by μ, [D-ala(2), mephe(4), gly-ol(5)] enkephalin, or κ, U69, 593, opioids. Both opioid agonists inhibited NP-derived neurogenesis and astrogenesis via their corresponding receptors as determined by immunocytochemistry. By administering selective inhibitors, we found that opioid inhibition of NP-derived astrogenesis was driven via extracellular-signal regulated kinase (ERK), while the p38 MAP kinase pathway was implicated in opioid attenuation of neurogenesis. In addition, μ and κ opioids stimulated oligodendrogenesis from NP-derived NG2(+) oligodendrocyte progenitors via both ERK and p38 signaling pathways. Accordingly, both opioids induced ERK phosphorylation in NG2(+) cells. These results indicate that small molecules, such as MOR and KOR agonists may play a modulatory role in NP terminal differentiation.